PENEGAKAN HUKUM TINDAK PIDANA LINGKUNGAN PEMBAKARAN HUTAN DAN LAHAN TERHADAP KORPORASI OLEHKEPOLISIAN DAERAH RIAU RIAU - Ryan Richardo; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Forest fires in Indonesia can not be separated from the poor pattern of land and forest policy in the country. Regular forest fires for a decade are not solely due to changes in ecological links. However, it is influenced by the deliberate element of large-scale plantation business actors in land clearing. Including also the negligence of industrial business actors, and the process of uncontrolled permission to control the territory. This shows that the monitoring and prevention of forest and land fires in Riau province is still very weak. More than 300 fire points in Riau this year are within HTI concession areas and plantations. It shows, the process of issuing permits for the plantation of the government is based on studies that memadai.Sebagai form of responsibility, the government should immediately revoke the operating license in points concessions experiencing the fire. The case of forest and land fires in Riau Province involving corporations that can provide great impact on social life, it should be obliged also to respect the fundamental values of our society which is determined by the criminal law.Based on the description above, the authors take the title of thesis that is "Enforcement of Environmental Criminal Law by Corporations in Riau Province Police Territory". As for the principal problems discussed in this study is the first How Law Enforcement against Crime Environmental Combustion of forest and land to the corporation by the Riau Police, Second Any obstacle in Law Enforcement terhadapTindak Criminal Environmental Combustion of forest and land to the corporation by Riau Police.As for the population and sample in this research is Kasubdit. IV. Ditreskrimsu Polda Riau, Investigator Dikrimsus Polda Riau, Director Jikalahari, The method used in this research is qualitative method. views of its kind research was conducted using normative law research, while nature is descriptive, considering the number of population is relatively small, then the entire population as respondents by census From the discussion Enforcement in Crime Environmental Combustion of forest and land to the Corporation by Police Riau as one of the efforts to combat the criminal acts Burning forest and Land of the Corporation based on the existing law, which, as a result of the burning of forest and land can cause much harm either to the government, the forest along with the environment and the ecosystem, the community of all life Which began to rare both the flora and fauna, law enforcement against forest and land burning experienced various obstacles. It is caused by several factors: the juridical constraints, geographical factors, the Fund Limitations In the Process of Law Enforcement, Lack of Facilities and Infrastructure Law Enforcement, Weak coordination among law enforcement, Factor seriousness, awareness and assertiveness competent officer.Keywords: Law Enforcement, Environmental Crime, Corporations, Riau Police